Liability of Intermediary Parties in the Context of Copyright Protection: A Case Study of 41pk/Pdt.Sus-Hk/2021 - Satrio, Bagas Putra; Wasitaatmadja, Fokky Fuad; Machmud, Aris (Universitas Muhammadiyah Tangerang, 2024)
In this study, the researcher aims to examine the practice of re-performing songs, commonly referred to as